2006
DOI: 10.1152/jn.01016.2005
|View full text |Cite
|
Sign up to set email alerts
|

Do Cortical Neurons Process Luminance or Contrast to Encode Surface Properties?

Abstract: Vladusich, Tony, Marcel P. Lucassen, and Frans W. Cornelissen. Do cortical neurons process luminance or contrast to encode surface properties ? J Neurophysiol 95: 2638 -2649, 2006. First published December 28, 2005 doi:10.1152/jn.01016.2005. On the one hand, contrast signals provide information about surface properties, such as reflectance, and patchy illumination conditions, such as shadows. On the other hand, processing of luminance signals may provide information about global light levels, such as the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 63 publications
6
23
0
Order By: Relevance
“…Friedman et al (2003), however, found no evidence for color filling-in signals in V1 and V2 of awake behaving monkeys. Recent modeling work suggests that the majority of V1 responses reported by Kinoshita and Komatsu (2001) can be understood on the basis of local and mean luminance processing and that only a small minority of responses are consistent with edge-driven surface activity, such as brightness filling-in (Vladusich et al, 2006). We speculate that the properties of these previously determined surface-responsive neurons (Rossi et al, 1996;MacEvoy et al, 1998;Rossi and Paradiso, 1999;Hung et al, 2001;Kinoshita and Komatsu, 2001;Roe et al, 2005) may in fact arise from the mechanisms underlying the extended edge responses we observed in our study, and so are presumably not directly related to our perception of brightness, color, or filling-in.…”
Section: Comparison To Neurophysiological Resultsmentioning
confidence: 99%
“…Friedman et al (2003), however, found no evidence for color filling-in signals in V1 and V2 of awake behaving monkeys. Recent modeling work suggests that the majority of V1 responses reported by Kinoshita and Komatsu (2001) can be understood on the basis of local and mean luminance processing and that only a small minority of responses are consistent with edge-driven surface activity, such as brightness filling-in (Vladusich et al, 2006). We speculate that the properties of these previously determined surface-responsive neurons (Rossi et al, 1996;MacEvoy et al, 1998;Rossi and Paradiso, 1999;Hung et al, 2001;Kinoshita and Komatsu, 2001;Roe et al, 2005) may in fact arise from the mechanisms underlying the extended edge responses we observed in our study, and so are presumably not directly related to our perception of brightness, color, or filling-in.…”
Section: Comparison To Neurophysiological Resultsmentioning
confidence: 99%
“…Geisler et al (2007) also showed that most of the neurons in the primary visual cortex carry substantial local luminance information, although we note that our local luminance changes are much smaller than the ones reported in this study. Vladusich et al (2006) also concluded that luminance processing predominates over contrast integration in the vast majority of surface-responsive neurons in V1, and Tucker and Fitzpatrick (2006) showed that layer 2/3 neurons of tree shrews' primary visual cortex, are sensitive to large-scale changes in luminance.…”
Section: Discussionmentioning
confidence: 99%
“…Simple cells in cortical area V1, which are often modeled as linear spatial filters followed by a threshold nonlinearity鈥攈ave also been alternatively modeled as having a linear dependence on log luminance (Kinoshita and Komatsu, 2001; Vladusich et al, 2006b), or log contrast (Tolhurst et al, 1983, their Figure 1). This suggests that the hypothesized logarithmic transformation might occur prior to the simple cell stage in V1.…”
Section: The Basic Neural Edge-integration Modelmentioning
confidence: 99%